PECULIARITIES OF ORGANIZATIONAL AND TECHNOLOGICAL SUPPORT OF INTERNATIONAL AIRPORTS OPERATIONS (REVIEW) - Vasylenko, Ihor; Yaremenko, Valentin; Lytvynenko, Sergiy (Science-based technologies, 2023)
The article is devoted to the study of key aspects of organizational and technological support of international airports operations in the modern global realities. The latest scientific researches on the development of airport activities were systematized and a significant scientific contribution of both domestic and foreign scholars to this issue was identified. No research has been found on the aspects of the development of international airports, taking into account the realities of wartime, which are relevant for Ukraine and the development of the entire airport complex as an inseparable system that allows to form a high-quality aviation product for both passengers and cargo clientele. A critical study of airport operations was provided, including ground handling, airfield services, billing and invoicing, and airport information management. It was noted that raising the standards of ground handling at specific airports will make it possible to involve air transport to a greater extent to serve more global supply chains, which is one of the key opportunities for the aviation industry development overall. It was found that the development of the non-aviation component of airport activities is a weakness of Ukrainian airports and accounts for only a small share of the revenue component. In the post-war period, the non-aviation component of Ukrainian airports should become a key driver of performance improvement and open new horizons for successful development. In analyzing the problems faced by airports at the current stage of development, it was revealed that the key ones are aviation security, cyber security, environmental safety and lack of competent personnel. For each of these problems, the authors present their own vision of the problem and ways to solve it. Significant differences in the development trends of Ukrainian airports and the world’s leading airports have been identified, manifested in a significant innovation gap and environmental issues. The ways of post-war development of domestic airports were proposed, taking into account the key aspects of pre-war development and opportunities that open up in the post-war period.